Evaluation of micro-drilling technologies for metal-injection-molded 420 stainless steel. Issue 3 (2nd July 2016) - Silverman, David E.; Chu, Bryan; Jacoby, Benjamin E.; Samuel, Johnson
ABSTRACT: Metal-injection-molded (MIM) 420 stainless steel is a commonly used material for high-value products such as fuel injector nozzles. However, the trade-offs involved in using different micro-drilling processes on this material are not well-documented in literature. This article presents a micro-drilling study of MIM 420 stainless steel using four candidate processes: micro-electrical discharge drilling (micro-EDD), ultrasonically assisted micro-EDD, micro-mechanical drilling (micro-MD), and ultrasonically assisted micro-MD. The micro-EDD results shows that the use of ultrasonic vibrations significantly improves the overall process time, spark erosion efficiency, and material removal rate of the process. However, this improvement comes at the expense of increased tool wear and surface roughness, especially while machining under high-discharge-energy conditions. The micro-MD results show that the use of ultrasonic vibrations is beneficial in lowering the thrust force, drilling torque, and tool wear at chipload values greater than the minimum chip thickness of the material. However, the ultrasonic vibrations do not have a notable effect on the surface roughness or on the size of the exit burrs. The results obtained from this study have been used to develop a Likert-type comparison scale to enable application-specific selection of micro-drilling processes for MIM 420 stainless steel.